The Impact of Clinical Pathway Implementation on Cost Effectiveness in Health Care Service: A Bibliometric Analysis - Farida Nur ‘Aini; Firman Pribadi (Green Publisher Indonesia, 2026)
Clinical pathways play a strategic role in mitigating fraud risk by reducing unnecessary variability in clinical practice. Implementing clinical pathways in hospital healthcare services has a positive impact on cost-effectiveness. To determine research trends related to the impact of clinical pathway implementation on cost-effectiveness in healthcare systems worldwide. This study used a bibliometric analysis approach. Data analysis techniques employed VOSviewer. VOSviewer tools were used for network, overlay, and density visualization. The bibliometric analysis in this study was conducted using VOSviewer software, employing a co-authorship analysis approach at the author level. This analysis identified 80 authors, with 18 authors showing the largest number of links. Implementing clinical pathways is an effective strategy for improving cost efficiency and the quality of healthcare services in hospitals. Clinical pathways need to be developed and implemented consistently to enhance cost-effectiveness, service quality, and the efficiency of the healthcare system, particularly in developing countries.